ANALISIS EMPIRIS LKPD BERORIENTASI MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP HASIL BELAJAR KETERAMPILAN PROSES SAINS PADA MATERI PESAWAT SEDERHANA DI KELAS VIII SMP NEGERI 8 PEKANBARU - Rahayu Tri Kurnia Sari; Zulhelmi Zulhelmi; Muhammad Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: PjBL IPA learners worksheets are worksheets that are prepared and designed with emphasis on the independence of learners in constructing their learning through project assignments. The main objective of this research is to develop a valid and practical PJBL-based science student worksheet on simple aircraft material for class VIII junior high school and to know the absorption of students science process skills. In this study the validation stage was carried out 2 times. The first validation was conducted by 5 validators, namely by 3 lecturers of FKIP UNRI and 2 experienced science teachers. The second validation was conducted by 2 validators, namely 2 science teachers in SMP Negeri 8 Pekanbaru. Next, the student worksheets were given to 40 students of class VIII at SMPN 8 Pekanbaru. This research instrument was in the form of a validation questionnaire, response questionnaire, and test results for learning science process skills. Data analysis in this study uses quantitative descriptive analysis by calculating the index of each indicator used to determine the validity and practicality of the worksheets students develop. The results of this study provide information about PjBL based science students worksheets developed on this simple plane material with very high categories, namely 92% content aspect, 88.75% construction aspect, 87% linguistic aspect, 90% graphic aspect. This PBPL LKPD has also been practical, for the questionnaire responses of teachers according to the very good category namely the content aspect of 93.33%, the construction aspect 83.33%, the 96.67% aspect, the graphic aspect 93.33%. Questionnaire responses of students in the category of very good, namely the aspect of content 88.86%, 82.83% construction aspects, linguistic aspects 89.75%, 89.25% graphic aspects. The absorption of students' process skills according to the category is quite good at 67.5%. Based on the results of the study, the worksheet developed by PjBL students can be used in learning to support the teaching and learning process so that it becomes better.Keywords: Student worksheet, Project Based Learning, Learning Outcomes Of Science Process Skills, Simple Aircraft.